Comparison of resmetirom quantative analysis in API and formulation models based on PXRD, FTIR and Raman scanning imaging combined with univariate and multivariate analyses - Yang, Chen; Luo, Ying; Sun, Wenxia; Liu, Xiangkui; Zhu, Xueyan (Talanta (Oxford), 2025)
Resmetirom is the first innovative drug for the treatment of non-alcoholic steatohepatitis (NASH), and its two crystal forms, form I and form-2H2O, were mentioned in the original patent. The commercially available crystal form of resmetirom was form I. However, the tablets were subject to temperature, pressure, and humidity, and may be converted to form-2H2O, which affects the bioavailability and efficacy. Therefore, it is crucial to establish a suitable crystalline quantification method to examine the concentration of both crystalline forms in APIs and formulations. The main objective of this paper was to test the feasibility of PXRD, FTIR and Raman for quantitative analysis of form I content in API and formulation models. Commonly used methods to establish quantitative modelling were univariate and multivariate analyses, due to the overlapping peaks in the FTIR and Raman spectra of two forms, only the multivariate method, with partial least squares regression (PLSR), was used, both univariate and multivariate analysis were utilized in PXRD since it has distinct single peaks. In the multivariate models, the raw spectra are preprocessed to remove interfering information and spectral noise by nine commonly used pretreatment methods. According to the result of this study, all four calibration models could be applied to the quantitative analysis of form I in two models; however, Raman was found to be the most appropriate model for both API model (Y = 0.99523X+0.00300, R2 = 0.9997, RMSECV = 9.32 %, RESEP = 0.29 %, RESEC = 0.19 %, LOD = 3.2819 %, LOQ = 9.9451 %, MSC pretreated) and formulation model (Y = 0.99456X+0.00331, R2 = 0.9996, RMSECV = 1.14 %, RESEP = 0.39 %, RESEC = 0.01 %, LOD = 3.3098 %, LOQ = 9.1029 %, WT pretreated). [Display omitted] •First report of resmetirom polymorph qualification in formulation models.•The Raman spectra of resmetirom of dihydrate and the anhydrous forms was reported for the first time.•Univariate and multivariate analytical models were established and compared.•PLSR models were constructed combined with pre-processing methods.